The HR Function of the 21st Century: A Critical Evaluation of its Contributions, Strengths and where it needs to Develop - Ekuma, Kelechi John (Advances in Social Sciences Research Journal, 2015)
There is a broad consensus among scholars and practitioners alike that maximising the potentials of human resources is central to organisational effectiveness and performance in the 21st Century global market place of intense social Darwinism. It has indeed been suggested that the way in which an organisation manages people can influence its performance. However, the relationship between effective Human Resource Management (HRM) function and organisational performance has remained a vexed issue among scholars, managers and even among HR practitioners. Indeed, there is an ongoing debate on what the HR function really contributes to organisations. The most fundamental issue remains how to understand how HRM practices impact on performance. Consequently, producing an unequivocal response to the question ‘what does HRM really contribute to organisational performance?’ has remained elusive. This article critically evaluates the contemporary HR function, with a view of highlighting its contributions to organisational effectiveness and performance. It argues that there are empirical evidences to suggest that there are clear linkages between effective HR function and organisational effectiveness and improved performance, but the greatest challenge remains how to quantify these contributions. The paper also notes that a lot can still be done to maximise these linkages and contributions; and concludes that for this to happen (i.e maximising HR’s contributions), HR must critically re-examine its functions and position itself to play a more strategic role in strengthening organisational capabilities and competencies and be proactive in its approach.